Distinguishing Dismissing From Fearful Attachment in the Association Between Closeness and Commitment. Issue 4 (May 2019) - Park, Yoobin; Debrot, Anik; Spielmann, Stephanie S.; Joel, Samantha; Impett, Emily; MacDonald, Geoff
When avoidantly attached individuals are simultaneously high in attachment anxiety, they are inclined to experience strong internal conflicts between seeking and avoiding closeness. This research examined whether the extent to which closeness, assessed as the inclusion of other in the self (IOS), is associated with greater commitment varies within individuals high in attachment avoidance as a result of differences in ambivalence toward maintaining the relationship. In two studies ( N 1 = 1, 604, N 2 = 2, 271), we found that the positive association between IOS and commitment was significantly weaker when attachment avoidance was combined with high (vs. low) attachment anxiety. In Study 2, we found lingering relational ambivalence even at high levels of IOS among individuals simultaneously high in attachment avoidance and anxiety, which in turn was related to relatively low commitment. Our findings highlight the role of relational ambivalence in avoidants' relationship functioning and the need to examine the interplay of the two attachment dimensions.